Physical Performance According to Body Fat Percentage and Fat-Free Mass in Chilean Young Amateur Soccer Players - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2025)
Objective: This study compared physical performance according to body fat percentage and fat-free mass in young amateur soccer players. Secondly, to analyze whether there is a correlation between body fat percentage and fat-free mass with physical performance. Methods: This is a cross-sectional study in which 65 youth amateur soccer players with a mean age of 16.8±5.14 years, distributed between below mean and above mean body fat percentage and fat-free mass, were analyzed. Results: The main results indicate the lower ball kicking speed dominant foot in players with above average body fat percentage (p=0.01; d=3.90; effect very large) and 20 m sprint ball (p=0.02; d=1.40 effect very large). While in fat-free mass above the mean in squat jump (p=0.00; d=1.70; effect very large), drop jump (p=0.00; d=1.91, very large effect), 10 m sprint ball (p=0.00; d=1.20; very large effect), 20 m sprint (p=0.00; d=0.83; very large effect), 20 m sprint ball (p=0.00; d=1.40; very large effect), foot dominant ball kicking speed (p=0.00; d=3.90; very large effect) and non-dominant ball foot kicking speed (p=0.00; d=2.80; very large effect). Conclusion: An above-average fat-free mass and below body fat percentage in young amateur soccer players leads to better jump performance, sprint speed, and ball-kicking speed. © 2025 Sociedad espanola de dietetica. All rights reserved.